The association between mean arterial pressure and outcomes in patients with cardiogenic shock: insights from the DOREMI trial. Issue 7 (12th August 2021) - Parlow, Simon; Di Santo, Pietro; Mathew, Rebecca; Jung, Richard G; Simard, Trevor; Gillmore, Taylor; Mao, Brennan; Abdel-Razek, Omar; Ramirez, F Daniel; Marbach, Jeffrey A; Dick, Alexander; Glover, Christopher; et al.
Abstract: Aims: Cardiogenic shock (CS) is a state of low cardiac output resulting in end-organ hypoperfusion. Despite high in-hospital mortality rates, little evidence exists regarding the optimal mean arterial pressure (MAP) target in CS. We therefore evaluated the relationship between achieved MAP and clinical outcomes in patients with CS. Methods and results: We performed a post hoc analysis of the CAPITAL DOREMI trial: a randomized, double-blind trial comparing dobutamine to milrinone in patients with CS. We divided patients into a high MAP group (average MAP ≥ 70 mmHg over the 36 h following randomization), and a low MAP group (average MAP < 70 mmHg). Our primary outcome included in-hospital all-cause mortality, resuscitated cardiac arrest, need for cardiac transplantation or mechanical circulatory support, non-fatal myocardial infarction, transient ischaemic attack or stroke, or initiation of renal replacement therapy. In total, 71 (37.0%) patients achieved an average MAP < 70 mmHg, and 121 (63.0%) achieved an average MAP ≥ 70 mmHg. The primary outcome occurred in 48 (67.6%) patients in the low MAP group and 51 (42.2%) patients in the high MAP group [adjusted relative risk (aRR) 0.70; 95% confidence interval (CI) 0.53–0.92; P = 0.01]. All-cause mortality occurred in 41 (57.8%) and 35 (28.9%) patients in the low and high MAP groups, respectively (aRR 0.56; 95% CI 0.40–0.79; P < 0.01). There were no significant differences in any secondary outcomes between each group. Conclusions: In patients with CS treated with inotrope therapy, low MAP is associated with worse clinical outcomes. Randomized data evaluating optimal MAP targets in CS is needed to guide medical therapy. Graphical abstract: